Biorreator de membranas de ultrafiltração aplicado ao tratamento de efluente industrial: avaliação da eficiência de tratamento e potencial de reúso da água - Farias, Amanda Paiva (2017)
The exalted population growth rate observed through the years reflects a higher water demand. This natural resource is not found homogeneous in state of nature and it becomes scarce in many regions, so the dispute over its use is one of the consequences. Given the delicate scenario, it is very important to adopt actions that provides the conservation of water in various activities. The industrial sector is responsible for a large part of the consumption of drinking water, maintaining the proportion for the generation and consequently discharge of effluents. The aim of this study was to evaluate the efficiency of the use of the Membrane Bioreactor (MBR) as a technology that provides better efficiency in the treatment of industrial effluents by means of replacing or combining this new technology with the conventional treatment. The effluent was characterized by physical-chemical parameters for this purpose. The LaCom was equipped with a 12L bench-scale bioreactor containing a flat plate of an ultrafiltration membrane, filled with effluents up to 10 L, for the monitoring of the removal efficiency in the biological treatment carried out. The analyzes realized were pH, sedimentable solids, Total Suspended Solids (SST), Chemical Oxygen Demand (COD) and Biological Oxygen Demand (BOD). Through the characterization of the effluent and the permeated, it was possible to calculate the average value for each parameter analyzed and the efficiencies of this treatment for some of the parameters. Total suspended solids presented 92.4%, COD analyzed with Pastel UV revealed 96.5 %, COD conventionally analyzed reached 99% and BOD 92.2%. The results allowed to verify and to prove the efficiency of the treatment of this type of industrial effluent by means of an ultrafiltration membrane. From analyzes and with the intention of applying the reuse in the industry, it was concluded that the permeated came out as expected, achieving a very satisfactory removal efficiency. Moreover, it can be reused in some industrial processes, always taking into account the type of process with the required quality. However, existing legislation and standards superficially addresses the reuse. When in fact it would be a priority to be discussed and applied in industries or other establishment.